Stenting for dysphagia due to recurrent malignant tumors - A. I. Ivanov; V. A. Popov; M. V. Burmistrov; M. A. Nazmeev (Вестник хирургии имени И.И. Грекова)
Introduction. Stenting for recurrent esophageal and gastric cancer to resolve dysphagia is a relatively rare intervention. Scientific publications devoted to this issue are very rare.The objective was to analyze the effectiveness, complications and life expectancy after esophageal stenting in patients with recurrent esophageal and gastric cancer after surgery.Methods and materials. Self-expanding metal esophageal stents were installed under videoendoscopic control in 45 patients with dysphagia due to esophageal and gastric cancer, for the period from 2013 to 2023, at the Republican Clinical Oncology Dispensary of the Ministry of Health of the Republic of Tatarstan named after M. Z. Sigal. RESULTS. There were no complications directly during the intervention. Dysphagia indicators decreased by an average of 2 points. In the early and late periods, complications arose in 16 cases (36 %), including stent migration, continued tumor tissue growth, granulation stricture, stent deformation, and pain syndrome. Ineffectiveness of stenting due to the impossibility of endoscopic resolution of the complications that arose was noted in three cases (19 % of the total number of complications). The average survival time was 128 days.Conclusion. Stenting in this category of patients is a fairly effective way to resolve dysphagia in a short time, but complications are quite common and not all of them can be resolved by endoscopic methods.